Team faultline: types, configuration and influence – evidence from China. Issue 3 (12th June 2017) - Zhang, Jing; Liang, Qiaozhuan; Zhang, Yue; Qu, Yuanmei (Elly)
Abstract : Purpose: This study aims to focus on three types of team faultlines (separation-based faultlines, variety-based faultlines and disparity-based faultlines) and discuss the different ways through which their configurational properties (faultline strength and faultline distance) affect team performance. Design/methodology/approach: The authors adopted panel data regression analysis to test the model. Panel data of Chinese provincial party-government top cadres teams that covers 30 provincial areas from 2007 to 2012 were collected for data analyses. Findings: The results revealed that separation-based faultline strength was negatively related to team performance, variety-based faultline strength had a U-shape relationship with team performance and disparity-based faultline strength had an inversed U-shape relationship with team performance. In addition, separation-based and disparity-based faultline distances served as moderators enhancing the curvilinear relationship between faultline strength and team performance. Notably, variety-based faultline distance failed to exaggerate the U-shape relationship between variety-based faultline strength and team performance; however, the relationship changed based on different levels of variety-based faultline distance. Originality/value: This study discussed team configurations based on three types of faultlines by comparing differences between team configurations reflected by diversity and faultline strength. Settled in Chinese political context, this study empirically tested the interaction effects between faultline strength and distance on team performance.